TRADISI MAPPENRE DUI’ DALAM PERNIKAHAN SUKU BUGIS PERSPEKTIF 'URF DI DESA MANURUNG KECAMATAN BOLA KABUPATEN WAJO - Asma Yunitah Alwi; Musyfikah Ilyas; Nurfaika Ishak (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
This study explores the mappenre dui’ tradition in Bugis weddings from the perspective of ‘urf in Manurung Village, Bola Subdistrict, Wajo Regency. It focuses on the process and significance of this tradition in Bugis marriage customs based on the concept of ‘urf. This field research employs a qualitative approach, utilizing documentation and interviews as data collection methods. The findings indicate that the people of Manurung Village practice the mappenre dui’ tradition as part of their cultural heritage, passed down through generations. It is an essential tradition, not only as a form of respect for women but also because it is primarily used to fund the entire wedding process. The mappenre dui’ ceremony includes several stages: mammanu’-manu’, followed by madduta (discussing the acceptance of the proposal, determining the dowry, wedding day, and the date for mappenre dui’), mappettuada (agreement), mappasiarekeng, and finally, the mappenre dui’ procession. From the perspective of ‘urf, each stage of the mappenre dui’ tradition aligns with Islamic law, categorizing it as ‘urf shahih.